Model of Based Physical Fitness Exercise Gurilapss Gymnastics (Mountain, Rimba, Ocean, Beach, River, Cultural Arts) Age 20-40 Years - Putri Permadi, Adinda Pasha; Hidayatulloh, Dede Taufik (Gladi : Jurnal Ilmu Keolahragaan, 2023)
Abstract This study aims to produce a GURILAPSS Gymnastics-based Physical Fitness training model for ages 20-40 years, and aims to test the effectiveness of this exercise model. This research is a research and development model from ADDIE which consists of 5 steps (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Data was collected through observation, filling out questionnaires and testing maximal oxygen volume by using the Rockport Walking Test to determine the level of cardiorespiratory endurance aged 42-40 years. Based on the results of the model effectiveness test using the experimental method and the one group pretest-posttest design approach. The sample in this effectiveness test was an experimental class of 40 people aged 20-40 years who were given the GURILAPSS Gymnastics-based Physical Fitness exercise model. The results of statistical calculations using paired samples t test for the experimental class show a significance value of 0.000 <0.05. The conclusion from the results of this study is that the GURILAPSS Gymnastics-based Physical Fitness training model can increase the cardiorespiratory endurance of people aged 20-40 years and is effectively used as a model of Physical Fitness exercises based on GURILAPSS Gymnastics for people aged 20-40 years. Keywords: Physical Fitness, GURILAPSS gymnastics, cardiorespiratory endurance